2000
DOI: 10.1177/03635465000280051301
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Reverse-Thread Screw Femoral Fixation on Laxity Measurements After Anterior Cruciate Ligament Reconstruction With Hamstring Tendon

Abstract: In arthroscopically assisted anterior cruciate ligament reconstruction using hamstring tendon graft, the graft rotates slightly as the femoral screw is inserted. Its final position tends to be in the anterior half of the tunnel in right knees, resulting in clinical laxity. To perform identical procedures on left and right knees, a reverse-thread screw was designed for femoral fixation in right knees. We prospectively studied 80 patients undergoing right-knee anterior cruciate ligament reconstruction with hamst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…12 The final position of the graft within the tunnel can vary with interference screw fixation, and this has been shown to have an effect on postoperative laxity. 18 In a previous study, it was identified that reverse-thread screws for femoral fixation in right-sided knees allows the graft to adopt a posterior position, which has been shown to significantly reduce the laxity seen in right-sided knee patients 12 months after surgery compared to standard screw fixation. 18 By eliminating this disparity between sides, a more valid comparison can be made between leftsided and right-sided knees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The final position of the graft within the tunnel can vary with interference screw fixation, and this has been shown to have an effect on postoperative laxity. 18 In a previous study, it was identified that reverse-thread screws for femoral fixation in right-sided knees allows the graft to adopt a posterior position, which has been shown to significantly reduce the laxity seen in right-sided knee patients 12 months after surgery compared to standard screw fixation. 18 By eliminating this disparity between sides, a more valid comparison can be made between leftsided and right-sided knees.…”
Section: Discussionmentioning
confidence: 99%
“…A standard 7 × 25-mm RCI interference screw was used for the left femoral fixation, and a reverse-thread 7 × 25-mm RCI interference screw was used for the right femoral fixation. 18 All patients signed informed consent forms. Ethical committee approval was obtained from the Australian Institute of Musculo-Skeletal Research and Sydney University.…”
Section: Patient Selectionmentioning
confidence: 99%
“…The 7 mm × 25 mm interference screws used for all fixations in this study were the only size available at the time (1993 and 1994). Subsequent analysis of these patients revealed some laxity in right knees 34 and in females with soft tibial bone. 12 These findings have been incorporated into current practice using undersized-diameter screws in hard bone such as on the femoral side, and oversized-diameter and longer screws in soft bone, which is usually on the tibial side.…”
Section: 2mentioning
confidence: 97%
“…3 To facilitate anatomic soft-tissue graft fixation, recent reports have described the use of direct tendon fixation with metal or biodegradable interference screws. 4,5 Although clinical data show promising results 6,7 and biomechanical studies have investigated the initial fixation strength of soft-tissue graft interference fit fixation, [8][9][10] there has been no analysis of the progression of tendon-to-bone healing using this fixation. Several animal studies have investigated softtissue graft-to-bone healing using nonanatomic graft fixation.…”
mentioning
confidence: 99%